AUDIT ENERGI LISTRIK GEDUNG BARU UNIVERSITAS MUHAMMADIYAH GRESIK - Yazid Nur Choir; Denny Irawan (Power Elektronik : Jurnal Orang Elektro, 2023)
Daily use of electricity is increasing because all human activity requires electrical energy. The energy audit is one way to reduce the rise in electrical energy. In case a new building at Muhammadiyah University of Gresik, Energy audits carried out in this building include the use of lighting and air conditioning. Based on the Minister of Energy and Mineral Resources of the Republic of Indonesia No. 13 of 2012 regarding saving electricity consumption, it is necessary to do electrical energy management so that the intensity of electricity consumption can be managed properly and can be more efficient. In this study an audit of the lighting system and air conditioning system was carried out and in this study the energy audit method was used by calculating the Energy Consumption Intensity (IKE) value for the process of electrical energy efficiency. From the initial energy audit calculations, the IKE value for the new building of Muhammadiyah University of Gresik was 671 kWh/m2/year, this value exceeds the ASEAN-USAID standard of 240 kWh/m2/year. Then the Energy Saving Opportunities (PHE) that will be implemented in the new building of the Muhammadiyah University of Gresik are changing the types of lamps, reducing the use of lights during the day, turning off the AC when not in use, and using inverter AC in the air conditioning system. Application of the above method to determine PHE decisions which will be implemented with the aim of not exceeding ASEAN-USAID standards.